Evaluation of brewers’ spent grain as a novel media for yeast growth - Sachindra T. Cooray (AMB Express, 2017)
Abstract Brewers’ spent grain (BSG) is a by-product generated from the beer manufacturing industry, which is extremely rich in protein and fiber. Here we use low cost BSG as the raw material for the production of a novel growth media, through a bioconversion process utilizing a food grade fungi to hydrolyze BSG. The novel fermentation media was tested on the yeast Rhodosporidium toruloides, a natural yeast producing carotenoid. The yeast growth was analysed using the growth curve and the production of intracellular fatty acids and carotenoids. Untargeted GCMS based metabolomics was used to analyse the constituents of the different growth media, followed by multivariate data analysis. Growth media prepared using fermented BSG was found to be able to support the growth in R. toruloides (21.4 mg/ml) in comparable levels to YPD media (24.7 mg/ml). Therefore, the fermented BSG media was able to fulfill the requirement as a nitrogen source for R. toruloides growth. This media was able to sustain normal metabolomics activity in yeast, as indicated by the level of fatty acid and carotenoid production. This can be explained by the fact that, in the fermented BSG media metabolites and amino acids were found to be higher than in the unfermented media, and close to the levels in YPD media. Taken together, our study provided evidence of a growth media for yeast using BSG. This should have potential in replacing components in the current yeast culture media in a sustainable and cost effective manner.